Pancreatic Endocrine Heterotopia Involving Meckel's Diverticulum: A Potential Mimic of Neuroendocrine Tumor. (April 2021) - Rowan, Daniel J.; Zhang, Lizhi; Logunova, Valentina
Pancreatic heterotopia most commonly occurs in the upper gastrointestinal tract, but can occur in other sites, including Meckel's diverticulum. When multiple histologic elements of the pancreatic tissue (acini, ducts, and endocrine cells) are present, the diagnosis is typically straightforward. In this article, we report a rare case of pure endocrine pancreatic heterotopia involving a Meckel's diverticulum, a potential mimic of a well-differentiated neuroendocrine tumor. Several features were useful in making the distinction, including lack of desmoplasia and mass forming lesion, and immunohistochemical staining in a physiological pattern similar to that of islets of Langerhans. It is important for pathologists to be aware of this entity and its features to avoid misdiagnosis of a neuroendocrine tumor.